UPAYA GURU AKIDAH AKHLAK DALAM MENGEMBANGKAN PERILAKU SISWA MTS NURUL JADID SURODINAWAN MOJOKERTO - Bahiyatul Lu’lu’ul Maulidiah; Ika Ratih Sulistiani; Ika Anggraheni (VICRATINA, 2019)
Regarding the behavior of students in MTs Nurul Jadid Surodinawan Mojokerto, according to the principal that each student has their own capacity. There are students who are difficult to manage and there are also students who can be arranged well. To see can be arranged or not seen by the way students obey the rules of order that are in school. Efforts made by the principal to support student behavior by forming positive characters in students. With religious activities, student behavior is well organized and organized. Education or teacher is a person who teaches and teaches because their rights and obligations are responsible for the education of students. in this study efforts can be understood as a planned goal by directing energy and mind. Thus  the teacher gives an understanding of students for the needs of students in the future. If  the teacher can provide an explanation or provide a more detailed description of it by using his own words and levels of thinking ability that is higher than memory or memorization